Doing Literary Texts with Young Children - Slunjski, Edita (Array, 2010)
The study analyses possibilities of modernising methodical approach in using literary texts in educational work with young and pre-school children. The quality of educational practice can be achieved by practitioners depending on their way of understanding it. Therefore, they need to be educated for researching practice together and for establishing a reflective dialogue with other participants in the educational process. In this work the authors present the action-ethnographic research used in training kindergarten and pre-school teachers for joint research and gradual improvement of their educational practice with a special emphasis on improving the quality of children’s experience of literary texts. During the research there was a gradual improvement of spatial, material and social conditions in the educational institutions, a more flexible time management of children’s activities was achieved, and teachers’ attitudes and beliefs were changing influencing their whole educational approach. Changes achieved in different organisational dimensions of the educational institutions led to gradual transformation of teachers’ methodical approach, which in time moved more and more away from the strict “analysis” of literary texts towards focusing on children and their individual and developmental needs. Results show that action-ethnographic research can also be regarded as a form of teachers’ continuous professional development in institutions of early and pre-school education.